2000
DOI: 10.1007/s002230010031
|View full text |Cite
|
Sign up to set email alerts
|

Acceleration of Fresh Fracture Repair Using the Sonic Accelerated Fracture Healing System (SAFHS): A Review

Abstract: The Sonic Accelerated Fracture Healing System (SAFHS) is a relatively new fracture management tool which incorporates the application of a specifically modified diagnostic ultrasound unit to healing fractures with the intention of accelerating repair. In an animal fracture model, this device has been shown to accelerate the rate of biomechanical healing by a factor of 1.4-1.6. In two randomized, controlled trials in humans, the same unit has been shown to reduce the time frame of clinical and radiographic heal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
50
0
8

Year Published

2006
2006
2017
2017

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 80 publications
(60 citation statements)
references
References 29 publications
2
50
0
8
Order By: Relevance
“…It has been reported that application of low-intensity pulsed ultrasound stimulation (LIPUS) promotes fracture healing and LIPUS has been clinically applied in the orthopaedic field [2,3], where positive effects of LIPUS on fracture healing of long bone were clearly concluded to reduce the time frame of clinical and radiographic healing by 38% [4]; however, effects of LIPUS on bone regeneration of flat bones in the cranial-maxillofacial area have not been abundantly documented although promotion of reossification ratio in rat noncritical-sized parietal bone defects by LIPUS or by low magnitude and high frequency mechanical stimuli has been recently reported [5,6] and although some clinicians have already performed LIPUS for bone augmentations in this area. Effects of LIPUS on bone regeneration in the cranial-maxillofacial should be carefully evaluated in animal experiments prior to its clinical trials.…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported that application of low-intensity pulsed ultrasound stimulation (LIPUS) promotes fracture healing and LIPUS has been clinically applied in the orthopaedic field [2,3], where positive effects of LIPUS on fracture healing of long bone were clearly concluded to reduce the time frame of clinical and radiographic healing by 38% [4]; however, effects of LIPUS on bone regeneration of flat bones in the cranial-maxillofacial area have not been abundantly documented although promotion of reossification ratio in rat noncritical-sized parietal bone defects by LIPUS or by low magnitude and high frequency mechanical stimuli has been recently reported [5,6] and although some clinicians have already performed LIPUS for bone augmentations in this area. Effects of LIPUS on bone regeneration in the cranial-maxillofacial should be carefully evaluated in animal experiments prior to its clinical trials.…”
Section: Introductionmentioning
confidence: 99%
“…While earlier reports showed that LIPUS enhances and accelerates repair of fractured bones (Heckman et al, 1994;Cook et al, 1997;Kristiansen et al, 1997;Hadjiargyrou et al, 1998;Mayr et al, 2000;Warden et al, 2000;Nolte et al, 2001;Jingushi et al, 2007;Walker et al, 2007;Griffin et al, 2008;Busse et al, 2009;El-Bialy et al, 2009), recent reports showed no difference in the healing of the LIPUS treated and nontreated fractured bones (Emami et al, 1999;Rue et al, 2004;Handolin et al, 2005;Lubbert et al, 2008). The controversial reports about the clinical success of using LIPUS in repairing bone fractures could be due to the difference in the proximity of the fractured bone to the LIPUS transducer.…”
Section: Therapeutic Ultrasound and Its Role In Enhancing Tissue Engimentioning
confidence: 97%
“…While stem cells are stimulated by LIPUS in a dose dependent response (Schumann et al, 2006a); the optimum LIPUS treatment for skin fibroblasts is 10 minutes per day (Zhou et al, 2004). Moreover, clinical applications using LIPUS has been accepted to be 20 minutes per day for 3-4 weeks (Heckman et al, 1994;Cook et al, 1997;Kristiansen et al, 1997;Hadjiargyrou et al, 1998;Mayr et al, 2000;Warden et al, 2000;Nolte et al, 2001;Jingushi et al, 2007;Walker et al, 2007;Griffin et al, 2008;Busse et al, 2009), in-vitro responses vary from one day to 21 days. It is to be remembered that in-vitro experiments allow direct effect of LIPUS to the cells, while in-vivo application suffers from LIPUS power attenuation as explained above.…”
Section: Therapeutic Ultrasound and Its Role In Enhancing Tissue Engimentioning
confidence: 99%
“…Rat coccygeal intervertebral disc tissues were also obtained as described previously. 9,10 The nucleus pulposus tissue was removed by cutting the annulus fibrosus transversely with a surgical knife under a dissecting microscope. The nucleus pulposus tissue was then digested in a mixture of 0.01% trypsin-EDTA solution (0.05% trypsin-EDTA, Gibco) for 30 min.…”
Section: Cell Isolation and Culturementioning
confidence: 99%
“…6 LIPUS has already been applied clinically to promote bone union in the treatment of fractures. [7][8][9] Iwashina and colleagues assessed the influence of LIPUS on rabbit intervertebral discs in vitro and found that it enhanced the ability of disc cells to proliferate and synthesize proteoglycans. 10 However, few studies have evaluated the influence of LIPUS on intervertebral discs and their constituent cells alone, and in particular cytokine pathways have received scant attention.…”
mentioning
confidence: 99%